2009
DOI: 10.1111/j.1574-6968.2008.01387.x
|View full text |Cite
|
Sign up to set email alerts
|

Free-living freshwater amoebae differ in their susceptibility to the pathogenic bacteriumLegionella pneumophila

Abstract: Legionella pneumophila is known as a facultative intracellular parasite of free-living soil and freshwater amoebae, of which several species have been shown to support the growth of the pathogenic bacteria. We report for the first time the behaviour of two strains (c2c and Z503) of the amoeba Willaertia magna towards different strains of L. pneumophila serogroup 1 and compared it with Acanthamoeba castellanii and Hartmannella vermiformis, known to be L. pneumophila permissive. In contrast to the results seen w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 23 publications
3
57
0
Order By: Relevance
“…That study also reported that strain Paris does not replicate in c2c Maky and Z503 willaertiae (Dey et al, 2009). Thus, our results when combined with the earlier study's findings indicate that W. magna strains can differ significantly in terms of permissiveness for different strains of L. pneumophila.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…That study also reported that strain Paris does not replicate in c2c Maky and Z503 willaertiae (Dey et al, 2009). Thus, our results when combined with the earlier study's findings indicate that W. magna strains can differ significantly in terms of permissiveness for different strains of L. pneumophila.…”
Section: Discussionsupporting
confidence: 74%
“…Indeed, aside from three studies that documented the intracellular growth of L. pneumophila in Echinamoeba exudans, Vahlkampfia jugosa and Willaertia magna (Dey et al, 2009;Fields et al, 1989;Rowbotham, 1986), very little is known about how L. pneumophila grows in its other known hosts. Hence, we incorporated L. pneumophila infection of W. magna into our analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results might be due to host amoebae, which adapt to and inhabit different environments (24,25). It has been reported that the growth of L. pneumophila in host amoebae depends on the bacterial genetic background (26,27). Hot spring isolates, which have unique STs adapted to amoebae, may be infectious to humans.…”
Section: Discussionmentioning
confidence: 99%
“…These features might be related to the kind of host amoebae, which adapt to and inhabit various environments (20,23). It has been shown that the growth of L. pneumophila in some species of host amoebae depends on bacterial genetic background (4,8). Some isolates with particular STs adapted for amoebae that live in bathwater may be infectious to humans.…”
Section: Discussionmentioning
confidence: 99%